Glioma Targeting and Anti-glioma Effect of Interleukin 13 Peptide and RGD Peptide Dual Functionalized Nanoparticles - Gao, Huile; Hu, Yue; Xiong, Yang; Zhang, Shuang; Yang, Jiarong; Yu, Lian; Jiang, Xinguo (Current Pharmaceutical Biotechnology, 2013)
Targeted nanoparticulated drug delivery systems have gained much attention owing to their potential in elevating anti-tumor effect and decreasing drug-originated side effects. In this contribution, a kind of dual glioma targeting delivery system was developed through co-modification nanoparticles with interlukin-13 peptide (IL-13p) and RGD peptide (IRNPs), in which IL-13p could target to IL13Rα2 on tumor cells and RGD could target to αvβ3 on neovasculature. The model drug, docetaxel (DTX), could release from the unmodified nanoparticles (NPs) and IRNPs at a sustained manner. In vitro, the uptake of IRNPs by C6 (a glioma cell line) cells was time- and concentration-dependent, which was significantly higher than the uptake of NPs and single modified nanoparticles. After loading with DTX, IRNPs induced the highest percentage of apoptotic cells. In vivo, DTX-loaded IRNPs induced obviously higher apoptosis of cells in glioma site. These results indicated the dual modification could improve the cellular uptake as well as antitumor effect, which demonstrated IRNPs were promising drug delivery systems for glioma targeting treatment.
Keywords: nanoparticles